Asuransi dan Perlindungan Hukum bagi Debitur KPR yang Wafat - Prabasiwi, Alberta Ira; Arifin, Zaenal; Subiadi, Rilda; Soegianto, Soegianto (Journal Juridisch, 2024)
Legal protection for deceased home ownership credit debtors based on insurance guarantees and Article 1100 of the Civil Code has not been clearly explained. The debtor's heirs do not yet know for sure about the risks. The purpose of this study is to analyze the implementation of legal protection for deceased home ownership credit debtors based on insurance guarantees and Article 1100 of the Civil Code. The research method uses empirical juridical using analytical descriptive. The results of this study are that the implementation of legal protection for deceased home ownership credit debtors does not only involve the debtor and creditor, but also the heirs if the debtor dies. This home ownership credit agreement is regulated in Articles 1320 and 1138 of the Civil Code. The agreement between the debtor and creditor also uses an offering letter as a credit agreement. The transfer of the debtor's heirs is regulated in Article 1100 of the Civil Code which states that heirs who receive an inheritance are required to share in the payment of debts, bequests, and other burdens. This is also related to the legal theory of Gustav Radbruch and Plato which regulates law. The principle related to this is the principle of consensualism related to article 1320 of the Criminal Code, namely freedom of contract. In the future, it is hoped that the heirs of the debtor will be more aware of the credit system so that they can avoid bad credit. Perlindungan Hukum debitur kredit pemilikan rumah yang meninggal dunia berdasarkan jaminan asuransi dan pasal 1100 KUHPerdata belum secara jelas dijelaskan. Ahli waris dari debitur belum mengetahui secata pasti mengenai resikonya. Tujuan penelitian untuk menganalisis pelaksanaan perlindungan hukum debitur kredit pemilikan rumah yang meninggal dunia berdasarkan jaminan asuransi dan pasal 1100 KUHPerdata. Metode penelitian menggunakan yuridis empiris dengan menggunakan deskriptif analitis. Hasil penelitian ini adalah pelaksanaan perlindungan hukum debitur kredit pemilikan rumah yang meninggal dunia tidak hanya melibatkan antara debitur dan kreditur, tetapi juga ahli waris apabila debitur meninggal dunia. Perjanjian kredit pemilikan rumah ini diatur dalam pasal 1320 dan 1138 KUHP. Perjanjian antara debitur dan kreditur ini juga menggunakan offering letter sebagai perjanjian kredit. Pengalihan ahli waris debitur diatur dalam pasal 1100 KUHP yang menyatakan bahwa ahli waris yang menerima warisan diwajibkan untuk ikut memikul pembayaran utang, hibah wasiat, dan beban-beban lain. Hal ini juga berkaitan dengan teori hukum Gustav Radbruch dan Plato yang mengatur hukum. Asas yang berhubungan dengan hal ini adalah asas konsesualisme yang berkaitan dengan pasal 1320 KUHP yaitu kebebasan berkontrak. Kedepannya diharapkan agar ahli waris debitur agar lebih mengetahui tentang sistem kredit sehingga terhindar dari kredit macet.